An economic analysis of twitching behaviour and species rarity. Issue 1 (2nd January 2021) - Brock, Mike; Fraser, Iain; Law, Cherry; Mitchell, Simon; Roberts, David L.
ABSTRACT: Avid birdwatchers, or 'twitchers', expend a considerable amount of money and time pursuing viewing experiences of rare or vagrant species. By vagrant species, we mean a species found outside its normal range/distribution. To enhance our understanding of this form of behaviour, we present results from a U.K. survey of twitchers. First, we examine the relationship between cost and rarity based on actual viewing experiences. Our statistical results reveal that the relationship between cost and rarity is positive and very inelastic. Second, we present results from a hypothetical Best-Worst Scaling exercise examining aspects of species rarity. We find that rarity is a more nuanced construct than simply the frequency with which a vagrant species has appeared. Our results provide insights into the meaning of rarity, as well as the economic value attach to it and why.